PENGARUH PROFITABILITY, LEVERAGE, SALES GROWTH, FIRM SIZE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP FIRM VALUE : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR CONSUMER NON-CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setyorini, Putri Indah; Cahyono, Yuli Tri (Jurnal Bina Bangsa Ekonomika, 2025)
Firm value is a description of investor confidence in the company through the process of activities for several years, namely when certain conditions have been achieved by a company. This study aims to determine the influence of profitability, leverage, sales growth, firm size, and corporate social responsibility on firm value. This study uses a quantitative method approach. The population in this study is non-cyclical consumer companies listed on the IDX in the 2021-2023 period. Sample selection was carried out using the purposive sampling method. The data analyzed is secondary data data. Data analysis uses multiple linear regression.  The results showed that the variables of profitability and leverage had an effect, while sales growth, firm size, and CSR had no effect on firm value